Laser-driven propulsion of multilayer graphene oxide flakes. Issue 9 (14th February 2018) - Qin, Chengbing; Qiao, Zhixing; He, Wenjun; Gong, Yani; Zhang, Guofeng; Chen, Ruiyun; Gao, Yan; Xiao, Liantuan; Jia, Suotang
Abstract : The laser-driven propulsion of multilayer graphene oxide flakes has been achieved by femtosecond laser irradiation. Abstract : Microjet engines have attracted significant research interest due to their fascinating capabilities to pick up, transport, and release various microcargoes. Here, we show that artificially designed multilayer graphene oxide (GO) flakes on a glass surface can be propelled by femtosecond laser irradiation, which is attributed to the rapid expansion and ejection of gases during the photoreduction of the GO by a femtosecond laser. The reduction of GO was characterized by Raman spectroscopy, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The ejection of gases was confirmed by the rising pressure in a vacuum chamber. The significant propulsion of GO flakes driven by femtosecond laser irradiation provides considerable promise for the design and fabrication of practical laser-driven micromachines toward a wide range of important future applications, with the features of wireless steering, short triggering time, and lack of toxicity.